Prevalence and treatment of atrial fibrillation in UK general practice from 2000 to 2016. Issue 1 (10th July 2018) - Adderley, Nicola Jaime; Ryan, Ronan; Nirantharakumar, Krishnarajah; Marshall, Tom
Abstract : Objective: Atrial fibrillation (AF) is the most common cardiac arrhythmia and an important risk factor for stroke. Treatment with anticoagulants substantially reduces risk of stroke. Current prevalence and treatment rates of AF in the UK as well as changes in recent years are not known. The aim of this analysis was to determine trends in age–sex specific prevalence and treatment of AF in the UK from 2000 to 2016. Methods: 17 sequential cross-sectional analyses were carried out between 2000 and 2016 using a large database of electronic primary care records of patients registered with UK general practitioners. These determined the prevalence of patients diagnosed with AF, the stroke risk of those with AF and the proportion of AF patients currently receiving anticoagulants. Stroke risk was assessed using CHA2 DS2 -VASc score. Results: Age–sex standardised AF prevalence increased from 2.14% (95% CI 2.11% to 2.17%) in 2000 to 3.29% (95% CI 3.27% to 3.32%) in 2016. Between 2000 and 2016, the proportion of patients with AF prescribed anticoagulants increased from 35.4% (95% CI 34.7% to 36.1%) to 75.5% (95% CI 75.1% to 75.8%) in those with high stroke risk (p for change over time <0.001) and from 32.8% (95% CI 30.5% to 35.2%) to 47.1% (95% CI 45.4% to 48.7%) in those with moderate stroke risk (p<0.001). In patients with low risk of stroke, the proportion decreased from 19.9% (95% CI 17.8% to 22.2%) to 9.7% (95% CI 8.4% to 11.1%) (p<0.001). Anticoagulant prescribing performance varied between practices; in 2016, the proportion of eligible patients treated was 82.9% (95% CI 82.2% to 83.7%) and 62.0% (95% CI 61.0% to 63.0%) in the highest-performing and lowest-performing practice quintiles, respectively. There was poor agreement in individual practice performance over time from 2006 to 2016: linear-weighted κ=0.10 (95% CI 0.02 to 0.19). Conclusions: From 2000 to 2016, the prevalence of recorded AF has increased in all age groups and both sexes. Anticoagulant treatment of eligible patients with AF has more than doubled, with marked improvements since 2011, alongside a reduction in the use of anticoagulants in ineligible patients with AF.